Hydrothermal Synthesis and Responsive Characteristics of Hierarchical Zinc Oxide Nanoflowers to Sulfur Dioxide - Qu Zhou; Bo Xie; Lingfeng Jin; Weigen Chen; Jian Li (Journal of Nanotechnology)
Sulfur dioxide, SO2, is one of the most important decomposition byproducts of sulfur hexafluoride, SF6, under partial discharge in GIS apparatus. The sensing performances of semiconductor gas sensors can be improved by morphology tailoring. This paper reported the synthesis method, structural characterization, and SO2 responsive characteristics of hierarchical flower-shaped ZnO nanostructures. Hierarchical ZnO nanoflowers were successfully prepared via a facile and simple hydrothermal method and characterized by X-ray powder diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy, respectively. Planar chemical gas sensor was fabricated and its responsive characteristics towards SO2 were systematically performed. The optimum operating temperature of the fabricated sensor was measured to be about 260°C, and the corresponding maximum responses were 16.72 and 26.14 to 30 and 60 ppm of SO2. Its saturated gas concentration was 2000 ppm with a response value of 67.41. Moreover, a quick response and recovery feature (7 s and 8 s versus 80 ppm of SO2) and good stability were also observed. All results indicate that the proposed sensor is a promising candidate for detecting SF6 decomposition byproduct SO2.